2008
DOI: 10.1103/physrevb.77.174409
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically asymmetric interfaces in aLaMnO3/SrMnO3superlattice due to structural asymmetries

Abstract: Polarized neutron reflectivity measurements of a ferromagnetic [(LaMnO3)11.8/(SrMnO3)4.4]6 superlattice reveal a modulated magnetic structure with an enhanced magnetization at the interfaces where LaMnO3 was deposited on SrMnO3 (LMO/SMO). However, the opposite interfaces (SMO/LMO) are found to have a reduced ferromagnetic moment. The magnetic asymmetry arises from the difference in lateral structural roughness of the two interfaces observed via electron microscopy, with strong ferromagnetism present at the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 18 publications
7
72
3
Order By: Relevance
“…In oxide heterostructures, it is known that surface segregation and polar discontinuities can be self-limiting processes for interfacial sharpness. [8][9][10] In the present study, such asymmetric profiles might be related to surface migration of Mn triggered by the difference in transition metal ionic radii. The polar discontinuity existing between STO and the LNO or LMO layers is expected to be resolved within the monolayers close to the STO substrate 36,37 and is thus unlikely to be the driving-force for the structural modifications observed at the LNO-LMO interfaces.…”
Section: Abstract: Interface Engineering Manganites Nickelates Magmentioning
confidence: 95%
See 1 more Smart Citation
“…In oxide heterostructures, it is known that surface segregation and polar discontinuities can be self-limiting processes for interfacial sharpness. [8][9][10] In the present study, such asymmetric profiles might be related to surface migration of Mn triggered by the difference in transition metal ionic radii. The polar discontinuity existing between STO and the LNO or LMO layers is expected to be resolved within the monolayers close to the STO substrate 36,37 and is thus unlikely to be the driving-force for the structural modifications observed at the LNO-LMO interfaces.…”
Section: Abstract: Interface Engineering Manganites Nickelates Magmentioning
confidence: 95%
“…Functionalities such as magnetic moment or conductivity have been shown to be drastically modified by such structural asymmetries. [8][9][10] In this letter, we demonstrate that it is possible to completely modify an interfacial property by changing the degree of material intermixing at the monolayer scale. To this end, we build a unique interface in a LaMnO3/LaNiO3 (LMO/LNO) bi-layer.…”
Section: Abstract: Interface Engineering Manganites Nickelates Magmentioning
confidence: 99%
“…In particular, soft x-ray reflectometry with variable photon energy and polarization can yield atomic layer-resolved profiles of the charge, 104 spin, 35 and orbital 46 polarization in oxide heterostructures and superlattices. Other noteworthy advances for potential probes is in spin-polarized neutron reflectometry, detecting the interface magnetic state, 105 and the ultra-slow positive muon probe attaining nanometer depth-profile resolution; 106 To conclude we have discussed the science of oxide interfaces from the viewpoint of emergent phenomena due to strong electron correlations. Combining advances in experimental techniques and new concepts supported by first-principles electronic structure calculations, this system will be an ideal arena for physics, chemistry, and also technology in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] In different all-manganite heterostructures, it has been observed that the properties of thin manganite layers may be modified with respect to their bulk behavior, for instance, by the appearance of a ferromagnetic moment in a nominally antiferromagnetic manganite 15,16,22 or by the formation of a ferromagnetic two dimensional electron gas at the interface between two antiferromagnetic insulating manganites. [10][11][12]14,[17][18][19][20] Orbital reconstruction, a modification of the orbital occupancy at interfaces between different materials, has also been observed.…”
Section: Introductionmentioning
confidence: 99%